Wounded Hearts: A Journey Through Grief - Moss, Colleen
Wounded Hearts: A Journey Through Grief is a series of annotated paintings created by CSUSM instructor, psychologist, and artist, Dr. Colleen Moss, after the sudden death of her husband. Depicting intense pain and despair, these paintings ultimately convey a message of hope, transformation, and the miraculous resiliency of the human spirit. This exhibit facilitates an understanding of the grief process and promote a dialogue about grieving in our personal lives and across cultures. Creating a "virtual exhibit" for Wounded Hearts: A Journey Through Grief enables the CSUSM community to continue to explore and interact with the exhibit. All paintings copyright (c) Colleen Moss. All photographs copyright (c) Frank Stair. To fully experience the exhibit, please download and open the accompanying PDF. It contains captions for the paintings as well as contextual information.